If we expand (3x^2 - 1)^4 we get, (3x^2 - 1)^4 = 81x^8 - 108x^6 + 54x^4 - 12x^2 + 1 If we derive (3x^2 - 1)^4 we get, (via chain rule) 24x(3x^2...

If we expand (3x^2 - 1)^4 we get, (3x^2 - 1)^4 = 81x^8 - 108x^6 + 54x^4 - 12x^2 + 1 If we derive (3x^2 - 1)^4 we get, (via chain rule) 24x(3x^2...

A solid is formed by attaching a hemisphere to each end of a cylinder. If the total volume is to be 120cm3, find the radius (in cm) of the cylinder that produces the minimum surface area. Express...

Differentiate y = (2x+5)^3(6x-1)^5. Express your answer in factored form.

Differentiate 2xy-17=-3x2 to find the slope at point (2,5). help?!

Picture of the questions: http://imgur.com/a/3D3yM

At what point is the tangent to the curve defined by the function f(x) = 4x2-x+5 parallel to the line y-15x=1? Help!

how do you prove that the derivative of x^n is nx^n-1

differentiate Y = 35+14x3+16x+10

y= 1/3x3+x2-35x+10 i)Determine the critical values and find out whether these critical values are maxima or minima ii) Determine the extreme values (y values) at the maxima...

Show that 3x + 4y + 25 = 0 is a tangent to the circle x^2 + y^2 = 25

A cube of ice is melting at a uniform rate. The initial volume of the cube is 20 cm^3, and the volume after five minutes is 15 cm^3. Find the rate at which the edge of the cube is decreasing after...

differentiate with respect to x ax^2+2hyx+by^2

Can you help me differentiate y=(4x^2+4)/5 and explain why you should not use the quotient rule for this?

differentiate with respect to x ax^2+2hyx+by^2

Business mathematics

-53x^2

if y=1+x+x^2/2!+x^3/3!=.............+x^n/n! then prove that dy/dx+x^n/n!=y

differentiation

The velocity v m s –1 of a particle at time t seconds, is given by v = 2t + cos2t, for 0 ≤ t ≤ 2. (a) Write down the velocity of the particle when t = 0. When t = k, the acceleration...

I', really stuck on this one HW question: I have to show how dC/dt = (D * (d^2C/dx^2)) + P at steady state (so when cD/dt =0) equals: (d^2C/dz^2) + (Pa^2/D...